Peran Keluarga, Interaksi Sosial, dan Teknologi dalam Pemerolehan Bahasa Anak Usia Dini - Welia c Sigalingging; Rosmawaty Harahap, Hidayat Herman; Cicilia Gultom, Rowimatul Hazizah; Sarah Eya Pepalemsa Br Ginting, Sarah Sofyanti br Siregar; Sry Eninta Br Bangun, Nailah Cahyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to integratively analyze the role of family, social interaction, and technology in the first language acquisition of early childhood. Language acquisition is a natural process that involves biological, cognitive, social, and cultural factors; however, in the modern era, technology also becomes a new variable influencing children's language development. This study uses a descriptive qualitative method with a literature review approach, based on 15 national and international articles published in the last 10 years. The review results show that the family serves as the main foundation in providing language stimulation from an early age through communication and language habits at home. Social interaction enriches children's language abilities through real communication experiences with peers and the surrounding environment. Meanwhile, technology has a dual role: as an educational tool that can expand vocabulary, but it also has the potential to cause speech delays when used excessively without guidance. Thus, language acquisition in early childhood is the result of the integration of these three factors. The balance between the role of the family, social interaction, and the wise use of technology is key to optimizing children's language development in linguistic, cognitive, and socio-cultural aspects.